Multimodal Imaging of Choroidal Structural in Torpedo Maculopathy - Yuan, Hao; Dou, Hongliang; Li, Xuemin (Frontiers in Medicine, 2023)
Objective: To report a case of torpedo maculopathy with multimodal fundus imaging methods, and firstly apply the choroid vascularity index to quantitatively describe the choroidal structural changes in torpedo maculopathy. Case presentation: An asymptomatic 41-year-old Chinese woman with an incidentally found yellowish-white macular lesion in her left eye was referred to our hospital. She denied any remarkable medical history. The best corrected Snellen visual acuity was 20/20 OD and 20/25 OS respectively. Fundus exam of her left eye revealed a well-circumscribed torpedo-like hypopigmented lesion in the macula region, and the tapered edge directed towards the fovea. Pigment deposition could be seen in the inferotemporal portion of the torpedo lesion. Fluorescein angiography showed the corresponding window defect without leakage and fundus autofluorescence demonstrated low autofluorescence throughout the lesion. Enhanced depth imaging optical coherence tomography (EDI-OCT) revealed outer retinal attenuation, subretinal cavitation, subtle inner choroidal excavation and thinning of outer nuclear layer. Choroidal vascularity index (CVI) calculated as the ratio of choroidal luminal area to total choroidal area was applied to display changes of choroidal structure. The results implied that subfoveal CVI of left eye seemed quite lower than that of right eye (OD 73.05% vs OS 64.00%). OCTA showed reduced density of the choriocapillaris in the temporal area of the lesion and increased capillary density in the nasal area. Functional examinations, including microperimetry, multifocal electroretinogram and static perimetry also revealed reduced retinal sensitivity, decreased stimulated amplitude and suspected scotoma in the lesion area. After 12 months of follow-up, the patient’s visual acuity and the clinical appearance of the lesion were unchanged. Conclusions: The torpedo maculopathy may be identified by abnormal appearance with multimodal imaging. Decreased choroidal vascularity in the lesion area measured quantitatively by choroid vascularity index may play a role in pathogenesis of torpedo maculopathy. Further TM classification may combine lesion appearance and location with OCT characteristics. Keywords: torpedo maculopathy; EDI-OCT; choroid vascularity index; multimodal imaging; classification